Mother’s parenting attitude and self-efficacy following care for child development program: A follow-up study - Pradipta, Afradilla Hanum; Haryanti, Fitri; Akhmadi, Akhmadi; Purwanta, Purwanta; Sitaresmi, Mei Neni (Universitas Aisyah Pringsewu, 2024)
Guidance by cadres to mothers on childcare within the CCD training was conducted in 2018. At that time, mothers exhibited positive attitudes and self-efficacy. However, two years later, the Covid-19 pandemic emerged, leading to a shift in circumstances and the discontinuation of the mentoring program. These changes could potentially alter the attitudes and self-efficacy that mothers possessed in caring for their children. This follow-up study aimed to examine the attitude and self efficacy of mother who participated in CCD training in Yogyakarta in 2018, comparing their status in 2022. This was a cross-sectional study. The respondents are mothers with children aged 4-6 years who have participated in mentoring by cadres during CCD training, totaling 57 individuals. The study employs attitude and GSES questionnaires adapted from Akhmadi's research (2021). Descriptive statistics are used to illustrate the findings, presenting data in terms of frequency, percentage, and mean. The mean score for maternal attitudes is (29.19), with (57.89%) categorized as less favorable and (42.10%) as favorable attitudes. The mean score for maternal self-efficacy is (30.38), with (68.42%) classified as low self-efficacy and (31.57%) as high self-efficacy. The research findings indicate a decline in maternal attitudes and self-efficacy in childcare post-CCD training in 2018.